Optimization of process parameters of self-purging microwave pyrolysis of corn cob for biochar production. Issue 11 (November 2021) - Quillope, John Christian C.; Carpio, Rowena B.; Gatdula, Kristel M.; Detras, Monet Concepcion M.; Doliente, Stephen S.
Abstract: Microwave pyrolysis offers rapid and low-cost technology to upgrade agro-forestry residues to high-value products. I-optimal experimental design was used to determine the optimal combination of microwave power and exposure time to maximize biochar yield from corn cob. A validation experiment at optimal conditions of 600 W and 6.9 min produced an average yield of 56.98% on a dry and ash-free basis, agrees with the predicted value (3.43% error) and confirms the adequacy of the model yield equation. Characterization of biochar product revealed an organized mesoporous structure with a carbon content of 62.68%, surface area of 3.05 m 2 /g, pore volume of 0.003 cm 3 /g, capacitance range of 27.14–53.99 μF/g, energy density range of 6.0 × 10 −7 - 1.2 × 10 −6 Wh/kg, and power density range of 9.4 × 10 −4 – 2.49 × 10 −3 W/kg. The biochar produced would require further process to be considered for various industrial applications. Abstract : Corn cob; Biochar; Microwave pyrolysis; Self-purging; Optimization; I-optimal design.